394. Pseudo-outbreak of Coagulase-negative Staphylococcus Species from Blood Cultures Highlights Unique Challenges in Care of Critically Ill Patients With COVID-19. (31st December 2020) - Park, Stacy; Attai, April E; Enfield, Kyle; Bell, Taison; Hill, Brandon; Carpenter, Rick; Cox, Heather L; Mathers, Amy
Abstract: Background: In response to the COVID-19 pandemic, a dedicated intensive care unit for patients infected with SARS-CoV-2 was created at our institution. We noticed a marked increase in the number of blood cultures positive for coagulase-negative Staphylococcus species (CoNS) that highlights unique challenges that arise with the creation of new units and workflows. Methods: We reviewed all blood culture results from the COVID-19 intensive care unit (CoVICU) from April 15 to May 29. We reviewed all blood cultures taken from the oncology ward, medical intensive care unit (MICU), and emergency department (ED) for the same time frame as a comparison. We calculated contamination rates, using the clinical microbiology laboratory criteria for possible contaminants based on species and number of positive blood cultures. Results: There were 324 total blood cultures collected from the CoVICU with 27/324 (8.3%) positive for organisms deemed contaminant, 10/324 (3.1%) were positive considered bloodstream infections (BSI); the ratio of BSI:contaminant was 1:2.7. For the MICU, ED, and oncology units contamination rates were 2/197 (1%), 33/747 (4.4%), and 2/334 (0.6%), respectively; and the ratio of BSI:contaminant was 5:1, 2.2:1, and 17.5:1, respectively. There was a significant relationship between contamination rates and unit, X 2 (3, N = 1602) = 30.85, p < 0.001. Conclusion: Upon investigation, peripheral blood draw kits were not stocked in the CoVICU. Additionally, certain components of standard work for blood culture collection (e.g. glove exchange) could not be performed per usual practice due to isolation precautions. Peripheral blood draws were routinely performed by nurses in CoVICU and MICU while phlebotomy performed these in other comparison units. We suspect that lack of availability of blood draw kits and disruption of typical workflow in isolation rooms contributed to an unusually high number of contaminated blood cultures among patients admitted to the CoVICU. Notably, the CoVICU and MICU providers were the same pool of caregivers, further supporting a process issue related to isolation precautions. Institutions should be aware of the need for extra attention to supply chain management and examination of disruption to standard work that arise in the management of COVID-19 patients. Disclosures: All Authors : No reported disclosures